PENGGUNAAN DEIKSIS PADA RUBRIK GAGASAN DALAM KORAN HALUAN RIAU - Minandar, Shintia; Sinaga, Mangatur; Charlina, Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research study about The Use of Deiksis in Gagasan Rubric in Haluan Riau Newspaper. This Research also study about type and mean of deixis description found by a Gagasan rubric in Haluan Riau newspaper. This Research use the approach qualitative and descriptive method which aim to to identify the type and describe mean of deixis that found on Gagasan rubric in Haluan Riau newspaper. Result of research in the form of identifying type and describe mean from deixis found [at] Gagasan rubric in Haluan Riau newspaper. Result of this research also as form of documentation of deixis that exist in Gagasan rubric in Haluan Riau newspaper.Keywords: Deixis, rubric Gagasan, Haluan Riau Newspaper